PEMETAAN ZONA RISIKO GERAKAN MASSA TANAH DAN BATUAN DESA KARANGSARI, KECAMATAN PENGASIH, KABUPATEN KULONPROGO, PROPINSI DAERAH ISTIMEWA YOGYAKARTA - , ARIF PRATAMA R ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Landslide disaster is one of the most frequently occurring each year in Indonesia and the location of the research is a risky place of the mass movement. This study was conducted to determine the level of risk generated mass movement based on the level and extent of potential vulnerabilities mass movement. In order to minimize the impact of losses incurred. Construction stage research with field geology investigation based on several parameters. Determination of potential zones and zones of vulnerability determined that each parameter has particularly different values. Zone of potential mass movement based on parameters such as slope, lithology, structural geology and land use while the mass movement hazard intensity level based on the parameters of the population and infrastructure activity. In the determination of the mass movement risk zones include all the parameters of the zone and the potential for mass movement hazard. Results of analysis showed the risk zones in the study area are divided into three zones, they are zone mass movement with high level of risk, zone of moderate mass movement, and a zone of low-level risk of mass movement. In order to reduce and prevent the occurrence of mass movements, they need some efforts from another people too such as knowing the early symptoms of a mass movement and make a retaining wall on the cliffs prone to landslide.